The Effect Of Promotion, Price, And Customer Experience On Consumer Purchase Decisions In Using Shopee E-Commerce - Nadin Miranda Rambe; Zufrie Zufrie; Elida F.S Simanjorang (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study examines the effect of promotion, price, and customer experience on purchasing decisions of Shopee E-Commerce users in Kampung Padang, Labuhanbatu Regency. A quantitative approach was employed using multiple linear regression analysis. Hypothesis testing was conducted partially using the t-test at a significance level of 0.05, with a t-table value of 1.986. The test results show: the promotion variable obtained t-count of 2.799 > t-table (1.986) and a significance of 0.026 < 0.05; the price variable obtained t-count of 2.135 > 1.986 with a significance of 0.035 < 0.05; the customer experience variable obtained t-count of 5.901 > 1.986 with a significance of 0.000 < 0.05. All three independent variables promotion, price, and customer experience are proven to have a positive and significant partial effect on purchasing decisions. These findings indicate that improved promotion quality, appropriate pricing, and positive customer experience increase consumers' tendency to make purchasing decisions. The results of this study are expected to provide a reference for business actors in formulating effective marketing strategies.